To determine which equation has a solution of \(-\frac{1}{2}\), we can substitute \(-\frac{1}{2}\) into each equation and see if it satisfies the equation.
-
Equation: \(x + \frac{1}{2} = -1\)
Substitute \(x = -\frac{1}{2}\):
\(-\frac{1}{2} + \frac{1}{2} = -1\)
\(0 \neq -1\) (not a solution) -
Equation: \(x + 1 = \frac{1}{2}\)
Substitute \(x = -\frac{1}{2}\):
\(-\frac{1}{2} + 1 = \frac{1}{2}\)
\(\frac{1}{2} = \frac{1}{2}\) (this is a solution) -
Equation: \(x - 1 = -\frac{1}{2}\)
Substitute \(x = -\frac{1}{2}\):
\(-\frac{1}{2} - 1 = -\frac{1}{2}\)
\(-\frac{3}{2} \neq -\frac{1}{2}\) (not a solution) -
Equation: \(x - \frac{1}{2} = 1\)
Substitute \(x = -\frac{1}{2}\):
\(-\frac{1}{2} - \frac{1}{2} = 1\)
\(-1 \neq 1\) (not a solution)
From this analysis, the equation that has a solution of \(-\frac{1}{2}\) is: \(x + 1 = \frac{1}{2}\).